Covalent-Assembly Based Fluorescent Probes for Detection of hNQO1 and Imaging in Living Cells - Han, Jialing; Cheng, Longhao; Zhu, Ya; Xu, Xiaowei; Ge, Chaoliang (Frontiers in Chemistry, 2020)
Human NAD(P)H: quinone oxidoreductase (hNQO1) is an important biomarker for human malignant tumors. Detection of NQO1 accurately is of great significance to improve the early diagnosis of cancer and prognosis of cancer patients. In this study, based on the covalent assembly strategy, hNQO1-activated fluorescent probes 1 and 2 are constructed by introducing coumarin precursor 2-cyano-3-(4-(diethylamino)-2-hydroxyphenyl) acrylic acid and self-immolative linkers. Under reaction with hNQO1 and NADH, turn-on fluorescence appears due to in-situ formation of the organic fluorescent compound 7-diethylamino-3-cyanocoumarin, and fluorescent intensity changes significantly. Probe 1 and 2 for detection of hNQO1 are not interfered by other substances and have low toxicity in cells. In addition to quantitative detection of hNQO1 in vitro, they have also been successfully applied to fluorescent imaging in living cells.